Hand-foot skin reaction with sunitinib: A rare case report with review of literature - Suchibrata Das; Alok K Roy; Srutee Barman; Aritra Roy (Wolters Kluwer Medknow Publications, 2020)
Newer multi-kinase inhibitors (MKI) like sunitinib have changed the therapy of patients of renal cell carcinoma, hepatocellular carcinoma, and gastrointestinal stromal tumor. The use of sunitinib also led to cutaneous toxicity, known as hand-foot skin reaction (HFSR). We report a case of hand-foot skin reaction (HFSR) in an Indian patient being treated with sunitinib. Respective literature on this disorder is also reviewed.